Proposed new design for Gatsby Men’s Hair Salon at Lot 1 and 1 A, Medan Istana 6, Bandar Ipoh Jaya, 30000, Ipoh, Perak / Syed Mohd. Fitri Syed Hassan - Syed Hassan, Syed Mohd. Fitri (Faculty of Architecture, Planning and Surveying, 2008)
I decide to propose a new design for Gatsby Men’s Hair Salon. This project is based on the fact that there are a few salon offer services only for men. Even though it is not much different from women or unisex beauty centre, this type of salon only specialized in men’s hair styling and treatment. Apart from that, the Japanese has been fully aware of men’s beauty and one of it is hair styling, so they craft and illustrated it to show the world that men’s hair can be in any type and forms, mostly like the so called J-Style. In the design of an interior space, the J-Style ingredient will be imploded into a salon space, with some street and modern facet. During this research some methods of research have been conceded out such as interviews, observation and mass media. And from the findings and research, a proposal of space requirements is carved out to be put in the design such as styling area, reception area, washing area, retail area and all. This proposed project’s site is located at the heart of Medan Istana, Bandar Ipoh Jaya, Ipoh. The results, issues and problems about surroundings, building and client’s need can be resolved by alternative ways of designing a space for a men’s salon. By giving an opening to this kind of project to prospect, it will give a good impression and a fine example for people to attempt new stuff and project in the near future.